Analysis of Waste Management and Community Participation in the Organization of Residential Area in Supporting Facilities - Istiqa, Suci; Sidabutar, Yuanita FD; Sitopu, Selli Dosriani (Borong Newinera Publisher, 2024)
Waste problems often occur, especially in Batam City, because the increase in population has an impact on increasing the amount of waste. Waste processing is a very important service and needs to be provided by the government. A waste processing pattern that involves community participation is the right decision. The implementation of community participation in Belian Village is still not implemented well. Thus, with the current problems it is interesting to carry out a study with the aim of examining waste management factors and community participation in the arrangement of residential areas in Balian Village, Batam City. Data collection techniques include interviews, questionnaires, observation and documentation. Sampling was carried out using the Random sampling method by taking samples at random. Based on the results of the research conducted, it can be concluded that waste processing in Belian Village starting from the stage of containerization, waste collection, waste sorting, waste processing, waste transportation and final waste disposal process is not optimal because waste sorting has not been carried out, while the role and participation of the community in Belian Village which is still lacking because there are still people who throw rubbish on the roadside or sidewalk. Forms of community participation in waste processing in the Belian sub-district are in the form of physical participation and money which are still lacking due to lack of initiative and community awareness in doing small things such as mutual cooperation.